ANALYSIS OF KINEMATIC MOVEMENT POSSIBILITIES OF PARA ATHLETICS - M.Mirjamolov (Research Focus International Scientific Journal, 2025)
This article analyzes the ability of Paralympic athletes to adapt to the loads of the annual training cycle and to restore the sports form on the basis of the kinematic description of the athletes’ nosological condition. The highest levels of training were also identified through special exercises in the laboratory. Based on the results of the study, proposals and recommendations on changes that need to be made at different stages of training of parasitologists have been developed.